Maternal depression and family adversity: Linked pathways to offspring depression? - Najman, J.; Plotnikova, M.; Williams, G.; Alati, Rosa; Mamun, A.; Scott, J.; Clavarino, A.; Wray, N. (2017)
© 2017 Elsevier Ltd There is conflicting evidence about the contribution of maternal depression and family adversity to depression experienced by offspring. Because maternal depression and family adversity are related, there is a need to determine how they independently contribute to offspring depression. Data are from a long-running prospective birth cohort study (Mater-University of Queensland Study of Pregnancy and its outcomes – MUSP). For this study some 2200 offspring were followed up at 30 years of age. We first examine the association between maternal depression and family adversity over the period from the pregnancy to the child reaching adulthood. Then we consider the extent to which maternal depression and family adversity trajectories over this period predict CIDI/DSM-IV episodes of depression in the offspring of these mothers at 30 years of age. We find a strong bi-directional association between maternal depression and family experiences of adverse life events over the entire period the child is at home. After adjustment, children reared in a family experiencing high levels of adverse life events are more likely to experience a lifetime ever DSM-IV diagnosis of depression, are more likely to have experienced multiple episodes of lifetime ever depression, and are more likely to report their first episode of depression was at a younger age. The findings suggest the association between maternal depression and offspring depression appears to be partly attributable to the higher levels of family adversity characteristic of depressed mothers.